Bold Stock Recommendations: Informative or Worthless? - Palmon, Dan; Sarath, Bharat; Xin, Hua C. (Contemporary Accounting Research, 2020)
ABSTRACT We select a small set of recommendations that lie in the upper and lower tail of the empirical distribution of divergences between a recommendation, and the consensus over the window (−30, −1) days prior to that recommendation. We classify these extremely divergent recommendations as bold, and then subdivide them into informative bold recommendations that lead other analysts (leading‐bold) and those that are ignored by other analysts (contra‐bold) based on the consensus change in the 30 days after the announcement. We focus on the information conveyed to the market by these bold, leading‐bold, and contra‐bold recommendations through their effects on cumulative abnormal returns (CAR). We find that bold recommendations are not anticipated by market participants (CARs are negative before a bold buy and positive before a bold sell). The next finding is that the market responds strongly to both leading and contra‐bold recommendations over the (0, +4)‐day window and that these reactions are stronger than that to nonbold recommendations. In contrast, over the longer (0, +30)‐day window, leading‐bold recommendations earn additional returns whereas contra‐bold ones reverse significantly due to lack of confirmation. The overall pattern is one of rational market reaction both in the short and long windows. We support the rationality of the market reaction by showing that the percentage of leading‐bold recommendations exceeds that of contra‐bold recommendations, and that these two types of recommendations cannot be separated using observable analyst characteristics such as experience or brokerage size.